2008
DOI: 10.1007/s00330-008-0887-z
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transarterial chemoembolization (TACE) of liver metastases from renal cell carcinoma: Local control and survival results

Abstract: The purpose was to evaluate the effectiveness of transarterial chemoembolization (TACE) in local tumor control and survival in patients with hepatic metastases from renal cell carcinoma (RCC). Prospective evaluation of TACE treatment outcome in 22 patients recruited from 1999 and 2005 was performed. The chemotherapeutic agent used was mitomycin only in 45% of the patients and mitomycin together with gemcitabine in the other 55%. The embolizing materials used in all of the patients were iodized oil (lipiodol) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…[57][58][59] This suggests that sequential TACE with preoperative PVE could also be potentially beneficial in patients with colorectal metastases. To date, however, no study has reported the using of sequential TACE with preoperative PVE in this category of patients.…”
Section: Sequential Tace and Pvementioning
confidence: 99%
“…[57][58][59] This suggests that sequential TACE with preoperative PVE could also be potentially beneficial in patients with colorectal metastases. To date, however, no study has reported the using of sequential TACE with preoperative PVE in this category of patients.…”
Section: Sequential Tace and Pvementioning
confidence: 99%
“…The overall recurrence rate of HCC patients with initial remission following TACE is very high. Therefore, anticancer drugs with high efficacy should be developed to overcome HCC [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of TACE and laser induced ablation as treatment for non-colorectal and non-breast cancer liver metastases in our patients showed a mean survival of 40.8 months. Whereas in studies dealing with the use of TACE alone in similar patient groups showed lower survival times (5-21 months), with extended survival of up to 60 months in studies concerning only neuroendocrine primaries [10,20,23]. Results for the use of ablative techniques alone in the treatment of liver metastases have shown survival times of up to 48 months in patients treated with LITT and up to 37 months for radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 84%